An analysis of Teachers' Perception toward Scaffolding Model in teaching Reading at Senior High School in Padang - Ajnia Fahlista; Jufri Jufri (Universitas Negeri Padang, 2019)
This research is aimed to describe teachers’ perception toward Scaffolding Model in teaching reading at Senior high School in Padang viewed from making connection,Graphical Aids Analysis, Vocabulary Enrichment, Reading Aloud, Language Analysis, Prompting activities and Integration Activities. . The population of this research was teachers in SMAN 1, SMAN 7, and SMAN 8 Padang. The sample of this research was 6 teachers. Two teachers in each schools. The instrument used in this research was Questionnaire and Interview. The questionnaire and interview made based on seven aspects on Scaffolding Learning ModelKey words: Scaffolding, Perceptions